2013
DOI: 10.1016/j.chom.2012.11.010
|View full text |Cite|
|
Sign up to set email alerts
|

NleB, a Bacterial Effector with Glycosyltransferase Activity, Targets GAPDH Function to Inhibit NF-κB Activation

Abstract: Summary Modulation of NF-κB-dependent responses is critical to the success of attaching/effacing (A/E) human pathogenic E. coli (EPEC and EHEC) and the natural mouse pathogen Citrobacter rodentium. NleB, a highly conserved type III secretion system effector of A/E pathogens, suppresses NF-κB activation, but the underlying mechanisms are unknown. We identified the mammalian glycolysis enzyme glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as an NleB interacting protein. Further, we discovered that GAPDH intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 41 publications
4
122
0
Order By: Relevance
“…[141][142][143][144][145] In addition, the mouse pathogen Citrobacter rodentium, which imitates EPEC, delivers the effector NleB to O-GlcNAcylate, the host glyceraldehyde 3-phosphate dehydrogenase, thus disrupting its interaction with TRAF2 and arresting the NF-κB pathway. 146 …”
Section: Shigella Flexnerimentioning
confidence: 99%
“…[141][142][143][144][145] In addition, the mouse pathogen Citrobacter rodentium, which imitates EPEC, delivers the effector NleB to O-GlcNAcylate, the host glyceraldehyde 3-phosphate dehydrogenase, thus disrupting its interaction with TRAF2 and arresting the NF-κB pathway. 146 …”
Section: Shigella Flexnerimentioning
confidence: 99%
“…Recently, it has been reported that the mechanism is related to the role of GAPDH in TNF-induced NF-B activation (45). This function may be disrupted during pathogen infection as an important virulence strategy used by attaching/ effacing pathogens to inhibit the host NF-B-dependent innate immune responses.…”
Section: Triplets Predicted Using the Candidate Nf-b/rela Modulators mentioning
confidence: 99%
“…In animal cells, GAPDH participates in multiple nonmetabolic processes, including apoptosis activation, S phase-dependent histone H2B transcription, DNA replication, DNA repair, and immune response to various diseases (Sirover, 1997;Zheng et al, 2003;Hara et al, 2005;Bae et al, 2006;Harada et al, 2007). GAPDH is also involved in NF-kB-dependent host innate immune responses, while pathogen effector NieB mediates O-GlcNAcylation of GAPDH to disrupt the TRAF2-GAPDH interaction and further suppresses TRAF2 polyubiquitination and NF-kB activation (Gao et al, 2013). In plants, GAPDHs have been implicated in embryo development, pollen development, root growth, lipid metabolism, seed oil accumulation, and abscisic acid signal transduction (Rius et al, 2006(Rius et al, , 2008Muñoz-Bertomeu et al, 2009Kim et al, 2013;Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%